Downside risk and hedge fund returns - Argyropoulos, Christos; Panopoulou, Ekaterini; Vrontos, Spyridon (Journal of Banking & Finance, 2025)
• We find a significant spread between the average returns of the high- and low-risk hedge funds. • Unlike HFs, the risk–return relationship for funds of hedge funds (FoHFs) is insignificant. • FoHFs do not compensate for risk-taking during market downturns. • Optimally weighted portfolios of HFs rank among the top 10% of FoHF performers. This study compares the predictive power of downside risk for hedge funds and fund of hedge funds returns. We find a positive relationship between downside risk and return for hedge funds but not for funds of hedge funds. This result is robust to the downside risk measure employed and additional control variables. Furthermore, we find that funds of hedge funds perform significantly worse than hedge funds during adverse equity market regimes, exhibiting an inverse (negative) risk–return relationship. Finally, we form realistic portfolios to determine whether an investor can construct a portfolio that outperforms the average fund of hedge funds. These portfolios display superior risk-adjusted performance and rank among the top performers of funds of hedge funds in our sample.